THE IMPACT OF INTELLECTUAL CAPITAL ON CORPORATE MARKET VALUE AND COMPETITIVE ADVANTAGE: A CROSS-SECTORAL LITERATURE REVIEW - Bukian, Putu Trisna Prabasari; Herawati, Nyoman Trisna (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study explores the role of intellectual capital (IC) in enhancing corporate market value and achieving competitive advantage across various industry sectors. The growing emphasis on knowledge-based assets highlights the strategic importance of IC as a driver of innovation and long-term value. Although prior studies have demonstrated the positive relationship between IC and firm performance, there is a lack of cross-sectoral insight, especially within emerging market economies, and limited focus on IC’s impact beyond financial metrics. Unlike prior literature which often centers on single-industry or country-specific contexts, this paper conducts a cross-sectoral review, identifying comparative insights, methodological limitations, and conceptual gaps in the understanding of IC’s influence on competitive advantage. The research employs a qualitative descriptive method in the form of a systematic literature review. It draws from top academic databases such as google scholar and neliti website. Thematic analysis was applied to identify patterns, gaps, and implications IC positively affects firm value in knowledge-intensive sectors like banking, while its impact is limited or inconsistent in industries such as plantations and financial services. Human capital emerges as the most influential component. The literature also highlights a heavy reliance on the VAIC™ (Value Added Intellectual Coefficient) model and limited focus on strategic, non-financial outcomes. Intellectual capital plays a strategic role in value creation across sectors. However, to fully leverage its potential, future research must expand in scope, method, and conceptual framing to reflect the evolving dynamics of global and knowledge-based economies.